2014
DOI: 10.2527/jas.2014-8137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of fulvic acid on lipid metabolism of finishing pigs1

Abstract: The experiment was conducted to investigate the effects of dietary supplementation of fulvic acid on lipid metabolism of finishing pigs. One hundred eighty crossbred barrows (Landrace × Yorkshire, 60 ± 2.5 kg) were randomly allotted to 5 dietary treatments (36 pigs/treatment) and fed a basal diet supplemented with 0, 0.2%, 0.4%, 0.6%, and 0.8% fulvic acid for 42 d. Thirty pigs (6 pigs/treatment) were slaughtered at the end of the experiment. Blood samples and adipose tissue were collected for determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
8
1
2
Order By: Relevance
“…In this context, increased intake of several dietary minerals have been associated with a reduced risk for developing MetSyn [22]. Additionally, fulvic acid was recently reported to stimulate insulin secretion in pigs without affecting glucose concentrations [23]. We did not observe any influence of OMC on either serum glucose or insulin levels in Chow-fed rats, but a pronounced glycemia-moderating effect was observed in HFD-treated rats.…”
Section: Discussioncontrasting
confidence: 52%
“…In this context, increased intake of several dietary minerals have been associated with a reduced risk for developing MetSyn [22]. Additionally, fulvic acid was recently reported to stimulate insulin secretion in pigs without affecting glucose concentrations [23]. We did not observe any influence of OMC on either serum glucose or insulin levels in Chow-fed rats, but a pronounced glycemia-moderating effect was observed in HFD-treated rats.…”
Section: Discussioncontrasting
confidence: 52%
“…Wang et al found that supplementation of humic substances (HS) yielded increases in ADG, G/F (HS 10%), and lymphocyte counts [ 57 ], but a decrease in backfat thickness. Chang et al confirmed that different doses of FA reduced pig backfat, and found that this was due to a higher activity of hormone sensitive lipase (HSL) and lower activity of lipoprotein lipase (LPL) [ 58 ]. Bai et al reported that dietary supplementation FA could increase G/F and reduce backfat thickness and malonaldehyde (MDA) in growing–finishing pigs [ 59 ].…”
Section: Organic Acidsmentioning
confidence: 99%
“…In human adipocytes, increased Ca 2+ levels can decrease cAMP levels through PDE activation, which consequently decreases HSL phosphorylation and ultimately inhibits lipolysis [ 9 ]. In a previous study of the adipose tissue of pigs indicated a significant decline in backfat thickness due to dietary supplementation of fulvic acid related to the increased activity of HSL [ 37 ]. We found that PDE1A (encoding PDE) and LIPE (encoding HSL) levels declined in the high-FE pigs, though the downward trends were not significantly different between two FE groups ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%